2019
DOI: 10.5688/ajpe7480
|View full text |Cite
|
Sign up to set email alerts
|

Work Profile Factors Identified From the Career Pathway Evaluation Program, 2018 Pharmacist Profile Survey

Abstract: Objective. To identify work profile factors from the Career Pathway Evaluation Program, 2018 Pharmacist Profile Survey. Methods. Exploratory factor analysis was used to describe the underlying structures (factors) that best represented respondents' work profiles. Descriptive statistics and Analysis of Variance were used to describe the 17 different work categories listed in the survey. Results. Eleven underlying factors were identified for the respondents' work setting profiles. A description of these factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Continuous career development is associated with and increases job satisfaction (Carvajal & Popovici, 2018;Mattsson & Gustafsson, 2020) (Schommer, Sogol & Brown, 2007;Schommer, Sogol & Brown, 2019). The university should provide information to all students on the merits and disadvantages of pharmacy education and related careers.…”
Section: Nakagomi and Hayashimentioning
confidence: 99%
“…Continuous career development is associated with and increases job satisfaction (Carvajal & Popovici, 2018;Mattsson & Gustafsson, 2020) (Schommer, Sogol & Brown, 2007;Schommer, Sogol & Brown, 2019). The university should provide information to all students on the merits and disadvantages of pharmacy education and related careers.…”
Section: Nakagomi and Hayashimentioning
confidence: 99%
“…There are other professional programs to assist schools in providing career orientation and awareness. Most colleges and schools utilize the APhA Career Pathway Evaluation Program, 7 typically early in the PharmD curriculum. The two national public awareness campaigns coordinated by AACP include profiles of diverse careers, including those associated with board certification through the Board of Pharmacy Specialties.…”
Section: How Does Early Career Guidance Contribute To the Ability To Prepare Clinicians?mentioning
confidence: 99%
“…Another survey indicated that independent community pharmacists rated the entrepreneurial aspect of their work highest ranked factor among all 47 profiles surveyed. 10 The entrepreneurial spirit is strong in independent community pharmacy and usually the motivating factor for this choice of vocation. The risk-taking capacity required for success in a highly competitive business space is required for a successful community pharmacist.…”
Section: Introductionmentioning
confidence: 99%